Knowledge mapping and current trends of global research on CRISPR in the field of cancer - Liu, Han; Lv, Zongwei; Zhang, Gong; Wang, Xia; Wang, Yuan; Wang, Kefeng (Frontiers in Cell and Developmental Biology, 2023)
Background: Gene editing tools using clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-related systems have revolutionized our understanding of cancer. The purpose of this study was to determine the distribution, collaboration, and direction of cancer research using CRISPR. Methods: Data from the Web of Science (WoS) Core Collection database were collected from 4408 cancer publications related to CRISPR from 1 January 2013 to 31 December 2022. The obtained data were analyzed using VOSviewer software for citation, co-citation, co-authorship, and co-occurrence analysis. Results: The number of annual publications has grown steadily over the past decade worldwide. The United States was shown, by far, to be the leading source of cancer publications, citations, and collaborations involving CRISPR than any other country, followed by China. Li Wei (Jilin University, China) and Harvard Medical School (Boston, MA, USA) were the author and institution with the most publications and active collaborations, respectively. The journal with the most contributions was Nature Communications (n=147) and the journal with the most citations was Nature (n=12,111). The research direction of oncogenic molecules, mechanisms, and cancer-related gene editing was indicated based on keyword analysis. Conclusions: The current study has provided a comprehensive overview of cancer research highlights and future trends of CRISPR, combined with a review of CRISPR applications in cancer to summarize and predict research directions and provide guidance to researchers.